2016
DOI: 10.1017/s1473550415000440
|View full text |Cite
|
Sign up to set email alerts
|

The potential of planets orbiting red dwarf stars to support oxygenic photosynthesis and complex life

Abstract: We review and reassess the latest findings on the existence of extra-solar system planets and their potential of having environmental conditions that could support Earth-like life. Within the last two decades, the multi-millennial question of the existence of extra-Solarsystem planets has been resolved with the discovery of numerous planets orbiting nearby stars, many of which are Earth-sized (and some even with moderate surface temperatures).Of particular interest in our search for clement conditions for extr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 70 publications
(105 reference statements)
2
42
0
Order By: Relevance
“…It was argued by Gale and Wandel (2017) that oxygenic photosynthesis in the PAR is feasible on planets around low-mass stars, primarily because the side facing the star (assuming synchronous rotation) will receive continuous illumination that compensates for the moderate photon flux. A detailed analysis of the prospects for photosynthesis on Proxima b was undertaken by Ritchie et al…”
Section: Photosynthesismentioning
confidence: 99%
“…It was argued by Gale and Wandel (2017) that oxygenic photosynthesis in the PAR is feasible on planets around low-mass stars, primarily because the side facing the star (assuming synchronous rotation) will receive continuous illumination that compensates for the moderate photon flux. A detailed analysis of the prospects for photosynthesis on Proxima b was undertaken by Ritchie et al…”
Section: Photosynthesismentioning
confidence: 99%
“…However, 16 years later, several of the assumptions in this work were found or shown to be inaccurate: terrestrial planets in the habitable zone, even of G-stars, were found to be frequent, M stars were shown to be less hostile to host planets with conditions life than previously thought (e.g. Tarter et al 2007;Seager and Demming 2010;Gale and Wandel 2016), and planets in the Habitable Zone of RDs were argued to be able to support liquid water and photosynthesis for a wide range of atmospheric and other properties (Wandel 2016). If RD planets are suitable for life this would imply that about half of the stars in the Galaxy could harbor a biotic planet and correspondingly enhance the potential abundance of civilizations.…”
Section: Introductionmentioning
confidence: 64%
“…Maximum GPP at 55 o N was found to be very high (in midsummer) resulting in an annual GPP (almost entirely produced in the summer months) reaching to about one third of that in the tropics (0±10 o latitude). By extrapolation, this should at least double the productivity on TLPs as calculated by Ritchie et al Furthermore, damaging levels of radiation would be avoided on TLPs, by the plants "selecting" locations with optimum radiation regimes, between the Sub-stellar point and light termination (Gale and Wandel 2017).…”
Section: Could Tlps Support Oxygenic Photosynthesis and Oxygen-rich Amentioning
confidence: 96%